2022
DOI: 10.1111/pedi.13312
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic outcomes of children 2–6 years of age with type 1 diabetes during the pediatric MiniMed670G system trial

Abstract: Background Highly variable insulin sensitivity, susceptibility to hypoglycemia and inability to effectively communicate hypoglycemic symptoms pose significant challenges for young children with type 1 diabetes (T1D). Herein, outcomes during clinical MiniMed™ 670G system use were evaluated in children aged 2–6 years with T1D. Methods Participants (N = 46, aged 4.6 ± 1.4 years) at seven investigational centers used the MiniMed™ 670G system in Manual Mode during a two‐week run‐in period followed by Auto Mode duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 24 publications
6
22
0
Order By: Relevance
“…GMI, glucose management indicator; SG, sensor glucose; SAP, sensor-augmented pump; TBR, time below range; TIR, time in range (50%). That was comparable or even better than the results reported for multicentre US pivotal studies in preschoolers 19 and school children. 18 In school children, this represents a doubling of the percentage of users achieving the target.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…GMI, glucose management indicator; SG, sensor glucose; SAP, sensor-augmented pump; TBR, time below range; TIR, time in range (50%). That was comparable or even better than the results reported for multicentre US pivotal studies in preschoolers 19 and school children. 18 In school children, this represents a doubling of the percentage of users achieving the target.…”
Section: Discussionsupporting
confidence: 82%
“…The present study found a high rate of TIR target achievement using the MiniMed 670G system in preschoolers (88%) and school children (50%). That was comparable or even better than the results reported for multicentre US pivotal studies in preschoolers 19 and school children 18 . In school children, this represents a doubling of the percentage of users achieving the target.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Exploration of AID systems in very young children has been sparse. The single system available for use in this age-group in both the U.S. and Europe resulted in mean ± SD HbA 1c 7.5 ± 0.6% (58 ± 6.6 mmol/mol) and increase in TIR to 63.8% (increase of 8.1%), while mean time with glucose level <70 mg/dL was unchanged at 3.2% (10). In a recent evaluation of the other system available in this age-group (Europe only), TIR was 71.6 ± 5.9%, while median time <70 mg/dL was 4.9% (11).…”
Section: Discussionmentioning
confidence: 99%
“…studies of AID systems have demonstrated improvement in glycemia without increased self-care burden (7)(8)(9); however, exploration of this technology in very young children has been sparse (10,11). It is critical to study new therapies that may allow more targeted glycemia in this age-group.…”
mentioning
confidence: 99%